2011
DOI: 10.1007/s11250-011-9843-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of time and dose of pregnant mare serum gonadotropin (PMSG) on reproductive efficiency in hair sheep ewes

Abstract: The aim of this study was to evaluate the effects of dose and application time of pregnant mare serum gonadotropin (PMSG) on reproductive performance of hair sheep ewes synchronized with fluorogesterone acetate (FGA) under tropical conditions of Northeastern Mexico. Ninety-nine hair ewes (63 Blackbelly and 36 Pelibuey) were treated with intravaginal sponges during 10 days. After insertion of FGA sponges, ewes were divided into four groups, and PMSG was injected intramuscularly at doses of 100, 200, and 400 IU.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 19 publications
(32 reference statements)
6
24
1
4
Order By: Relevance
“…On the other hand, fecundity was by 44% higher in ewes treated with 280 UI of PMSG, which is due to the numerical difference in single lambing observed in ewes treated with 140 IU, and to the presence of ewes that lambed 3 or 4 offsprings in the group treated with 280 IU. Under thermoneutral conditions, Quintero-Elisea et al (2011) found also higher fecundity percentage in Pelibuey and Blackbelly ewes treated with 200 IU of PMSG than in those treated with 100 IU. In general, these results suggest that low PMSG doses as 280 IU can be used in combination with FGA impregnated sponges to improve the lamb production in Pelibuey and Pelibuey × Romanov ewes during the season of high environmental temperatures.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, fecundity was by 44% higher in ewes treated with 280 UI of PMSG, which is due to the numerical difference in single lambing observed in ewes treated with 140 IU, and to the presence of ewes that lambed 3 or 4 offsprings in the group treated with 280 IU. Under thermoneutral conditions, Quintero-Elisea et al (2011) found also higher fecundity percentage in Pelibuey and Blackbelly ewes treated with 200 IU of PMSG than in those treated with 100 IU. In general, these results suggest that low PMSG doses as 280 IU can be used in combination with FGA impregnated sponges to improve the lamb production in Pelibuey and Pelibuey × Romanov ewes during the season of high environmental temperatures.…”
Section: Discussionmentioning
confidence: 74%
“…In hair and wool sheep, vaginal insertion of fluorogestone acetate (FGA) impregnated sponges for 10-12 days in combination with the administration of 400-500 IU of pregnant mare serum gonadotropin (PMSG) prior to or at time of sponge removal have been the synchronization and/or induction protocol more used worldwide, with acceptable results on response to estrus, fertility, and prolificacy (Barret et al, 2004;Avendaño-Reyes et al, 2007;Quintero-Elisea et al, 2011;Kermani et al, 2012). However, the protocol brings about elevated costs due to the high PMSG dose used, therefore economically this management strategy is little profitable for sheep producers.…”
mentioning
confidence: 99%
“…All the experimental ewes were treated with fluorogestone acetate vaginal sponges (40 mg; Chronogest, Intervet, Federal District, México) for 10 days. Then, the sheep were intramuscularly injected with pregnant mare’s serum gonadotropin (Ningbo Hormone Co., Ningbo, China) at a dose of 400 IU for synchronized oestrus41. All ewes were euthanized between 24 and 36 h after having reached spontaneous oestrus after one cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Then sponges were removed and pregnant mare serum gonadotropin (Ningbo Hormone Co., Ningbo, China) was injected i.m. at a dose of 400 IU into each sheep to synchronize estrus43. Twenty-four hours after spontaneous estrus was detected, all ewes were euthanized.…”
Section: Methodsmentioning
confidence: 99%